Environmental risk factors related to the incidence of wheeze and asthma in adolescence. Issue 1 (January 2015) - Hedman, L.; Andersson, M.; Bjerg, A.; Forsberg, B.; Lundbäck, B.; Rönmark, E.
Summary Background Asthma is common among adolescents, but there are few population‐based studies on the risk factors for incident asthma and wheeze at this age group. Objective To study risk factors for incident asthma and wheeze in adolescence. Method Within the Obstructive Lung Disease In Northern Sweden (OLIN) studies, a cohort of 3430 school children (age 7–8 year) was recruited in 1996. In the present study, this cohort was followed from age 12–19 year. At baseline (age 12 year), 3151 participated and skin prick tests (SPT) were performed. The cohort was resurveyed annually, and risk factors for the cumulative incidence of asthma and wheeze from age 12–19 year were analysed using multivariate Cox regression. Results Female sex (wheeze: HR 1.4 95%CI 1.2–1.6; asthma: HR 1.8 95%CI 1.2–2.5) and a positive SPT to cat, dog or horse at baseline (wheeze: HR 1.6 95%CI 1.2–2.1; asthma: HR 2.3 95%CI 1.4–4.0) were significantly associated with the cumulative incidence of wheeze and asthma. Increasing numbers of siblings were inversely related to the incidence of wheeze (HR 0.9 95%CI 0.8–0.97) and asthma (HR 0.8 95%CI 0.7–0.97). Parental asthma was related to the incidence of asthma (HR 1.8 95%CI 1.2–2.6) while ever smoking (HR 2.0 95%CI 1.6–2.4) and house dampness (HR 1.3 95%CI 1.1–1.6) were risk factors for the incidence of wheeze. Maternal ETS exposure increased the risk of incident asthma in non‐sensitized subjects (HR 1.9 95%CI 1.0–3.7). Conclusion and clinical relevance Several environmental risk factors related to the incidence of asthma and wheeze in adolescence were identified and may be possible targets for intervention and prevention.